English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

write them so they can be added top to bottom (i.e. line up the x's, y's, and constants):

4x + 2y = -4
x - 2y = -3 (we need to rearrange the original equation here to line things up)

now add top to bottom:

(4x)+(x) + (2y)+(-2y) = (-4)+(-3)
5x + 0 = -7
5x = -7
x = -7/5

now plug x in to either equation to solve for y:

2y = -7/5 + 3
2y = -22/3
y = -22/6 = -11/3

Hope this helps :)

2006-11-10 09:56:46 · answer #1 · answered by disposable_hero_too 6 · 0 1

replace the 2Y in the first equation with the 2Y (which = x + 3) from the second.

(x+3) +4x = -4

5x = -7

x = -7/5
then plug that back in to the second equation to find y
2Y= (-7/5) +3
Y= 4/5

check your answer with the first equation
2(4/5) + 4 (-7/5) = -4
8/5 + -28/5 = -4
-20/5 = -4
-4 = -4
so the answers are correct.

2006-11-10 18:00:08 · answer #2 · answered by scurvybc 3 · 1 0

2y+4x= -4
2y=x+3

x = 2y-3

2y + 4(2y-3) = -4
2y + 8y - 12 = -4
10y = 8
y = 4/5

x = 2(4/5) - 3
x = [8/5] - 3
x = -7/5

2006-11-10 17:57:44 · answer #3 · answered by bourqueno77 4 · 0 0

fedest.com, questions and answers